Glotopolitics and Orthographic Regulations Among Internet Users During the Colombian National Strikes of 2019 and 2021 - Olave Arias, Giohanny (2024)
This paper aims to analyze the spelling regulations implemented by Facebook and Twitter users during the national strikes of 2019 and 2021 in Colombia. From a glotopolitical perspective, the study identifies the discursive constructions associated with spelling adequacy in virtual interventions (comments and posts) as well as in public spaces (graffiti) within the context of these social movements. The topoï that support these discourses are located, and the argumentative strategies employed by individuals in their publications are highlighted. The analysis focuses on the underlying ideologemes of these interventions and reveals that both proponents and opponents of the strikes share conservative perspectives regarding spelling, often linking it to factors such as education level, intelligence, and criminality. Finally, the research uncovers a relationship between the unrestricted surveillance of spelling regulations and the defense of social regulation.